PEMBERDAYAAN RADIO KOMUNITAS SEBAGAI MEDIA INFORMASI DI TAPAL BATAS PAPUA - Christiany Juditha (Profetik: Jurnal Komunikasi, 2015)
The existence of community radio broadcast in Indonesia growing rapidly, as more open access to information, technology advances, and the community the opportunity to use the media for solving the problems of the community, including in the border region with neighboring Indonesia. However, community radio has a number of issues including, lack of community participation itself, a factor of Human Resources, lack of budget, and lack of infrastructure. The purpose of this research is to get an idea of empowerment ‘Suara Kerom’ community radio in Asyaman as a medium of information at the border between Indonesia and Papua New Guinea.This study uses a case study method with a qualitative approach. The study concluded that the Human Resources ‘Suara Kerom’ was minimal and limited. Infrastructure which is the assistance of the Ministry of Communications and Information Technology sufficient. While the broadcast content is good for such a talk show about family, local governments and entertainment events. Unfortunately, because of damage to the equipment so that the radio transmitter is no longer on the air a few months, so that can not be empowered to carry out its role and function as a medium of information as appropriate.